The African participation at the World Trade Organization : legal and institutional aspects : 1995-2010 - Apecu Laker, Joan (Graduate Institute of International and Development Studies (Series) ;, 2014)
Through substantive investigation, African Participation at the World Trade Organization: Legal and Institutional Aspects, 1995-2010 offers thorough explanations for the nominal, minimal, and largely ineffective activity of African members in the WTO, focusing on the three core areas of regular committee work, dispute settlement and negotiations, and considering the Group's size, compared to non-African Members. Fundamentally, the research examines the longstanding and continuing question in the Multilateral Trading System revolving around the substantive quality and effectiveness of African.